2007
DOI: 10.2172/910503
|View full text |Cite
|
Sign up to set email alerts
|

Home Performance with ENERGY STAR: Utility Bill Analysis on Homes Participating in Austin Energy's Program

Abstract: An example of the second type of inconsistency is shown by the following bills for premise number 2829400. The ending date for the first bill (3/17/2001) is consistent with the starting date for the second bill. However, there is no ending date for either the second or third bills and these bills have duplicate starting dates.An ending date for the second bill of 4/14/2005 can be derived from the number of days in the billing period (28). The missing ending date for the third bill can be filled as 5/20/2005, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Methods for disaggregating billing data have been previously described (ASHRAE 2002, Belzer 2007, Sondregger 1998. ASHRAE Guideline 14-2002 was reviewed for applicability to the task of disaggregating the large sample of PG&E billing data.…”
Section: Review Of Disaggregation Methods In the Literaturementioning
confidence: 99%
“…Methods for disaggregating billing data have been previously described (ASHRAE 2002, Belzer 2007, Sondregger 1998. ASHRAE Guideline 14-2002 was reviewed for applicability to the task of disaggregating the large sample of PG&E billing data.…”
Section: Review Of Disaggregation Methods In the Literaturementioning
confidence: 99%
“…In view of the long-run relationships between the household electricity consumption and other variables in the models, the long-run and short-run elasticities are further examined. The corresponding ARDL specifications of the long-run models are (5) and (6) for Singapore and Shanghai, respectively. As discussed in section 2.2.2, a maximum of 4 lags was employed in Eqs.…”
Section: Ardl Cointegration Analysismentioning
confidence: 99%
“…As discussed in section 2.2.2, a maximum of 4 lags was employed in Eqs. (5) and (6) and the optimal lag length is determined by minimizing the AIC. The specifications with the optimal lag length are ARDL(1,1,3,2) and ARDL(3,1,3,4) for Singapore and Shanghai, respectively.…”
Section: Ardl Cointegration Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A 2007 National Renewable Energy Laboratory and Pacific Northwest National Laboratory study of Austin Electric's HPwES program found that in more than 6,000 homes in Austin, Texas, the measured savings were in the range of 25%-35%, based on utility bill data (Belzer, 2007). These savings are in the range of BA goals.…”
Section: Introductionmentioning
confidence: 99%